Ferritinophagy was involved in long-term SiNPs exposure induced ferroptosis and liver fibrosis. Issue 2 (7th February 2023) - Liang, Qingqing; Ma, Yuexiao; Wang, Fenghong; Sun, Mengqi; Lin, Lisen; Li, Tianyu; Duan, Junchao; Sun, Zhiwei
Abstract: SiNPs could induce liver fibrosis invivo, but the mechanism was not completely clear. This study focused on exploring whether long-term SiNPs exposure at human-related exposure dosage could lead to ferritinophagy-mediated ferroptosis and liver fibrosis. In vivo, long-term SiNPs exposure induced liver fibrosis inrats accompanied by ferritinophagy and ferroptosis in hepatocytes. Interestingly, the progression of liver fibrosis was alleviated after exposure cessation and recovery, meanwhile ferritinophagy and ferroptosis were not further activated. In vitro, after long-term SiNPs exposure, the mitochondrial membrane ruptured, lipid peroxidation intensified, the level of redox active iron increased and the repair protein of lipid peroxidation were consumed in L-02 cells, demonstrating ferroptosis occurrence. Notably, NCOA4 knockdown inhibited ferritin degradation, alleviated the increase of intracellular ferrous iron level, reduced lipid peroxidation and the depletion of glutathione peroxidase 4 (GPX4). In conclusion, ferritinophagy mediated by NCOA4 was responsible for long-term SiNPs exposure induced hepatocytes ferroptosis and liver fibrosis, which provided a scientific basis for toxicological assessment of SiNPs and would be benefited for the safety design of SiNPs-based products.